2012
DOI: 10.1102/1470-7330.2012.0030
|View full text |Cite
|
Sign up to set email alerts
|

Blind spots at oncological CT: lessons learned from PET/CT

Abstract: Improved accuracy in oncological computed tomography (CT) could lead to a decrease in morbidity and improved survival for oncology patients. Visualization of metabolic activity using the glucose analogue [18F]fluorodeoxyglucose (FDG) in combination with the high anatomic resolution of CT in an integrated positron emission tomography (PET)/CT examination has the highest sensitivity and specificity for the detection of primary and metastatic lesions. However, PET/CT costs are high and patient access is limited; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
(46 reference statements)
1
8
0
Order By: Relevance
“…Other studies have reported similar results, with frequently missed lesions on radiologic examinations being pulmonary embolism, venous thrombosis, unexpected gastrointestinal tumors, and bone and soft tissue lesions such as metastasis (2,3,9).…”
Section: Jksronlineorgsupporting
confidence: 62%
See 1 more Smart Citation
“…Other studies have reported similar results, with frequently missed lesions on radiologic examinations being pulmonary embolism, venous thrombosis, unexpected gastrointestinal tumors, and bone and soft tissue lesions such as metastasis (2,3,9).…”
Section: Jksronlineorgsupporting
confidence: 62%
“…Occasionally, as in cases of neck or abdominal computed tomography (CT) scans, additional specific sites (i.e., a part of the chest) may inevitably be included and also need to be interpreted correctly. Incidental but potentially important findings outside the area of interest may be present but missed in any radiologic studies (2)(3)(4)(5)(6). We have occasionally found chest lesions that were not reported on neck CT interpretations when follow-up neck or chest CT studies were performed and compared with a previous neck CT study.…”
Section: Introductionmentioning
confidence: 98%
“…18 F-FDG is the most widely used radiolabeled agent (or tracer) which is actively taken up and accumulated in cancer cells [4]. Since 18 F-FDG PET/CT can detect cancer cells at cellular and molecular levels, it is regarded as the most sensitive and specified method among current imaging modalities [14][15][16].…”
Section: Pet Specialists and 18 F-fdg Pet/ctmentioning
confidence: 99%
“…These rates are based on the values found in the literature. [30][31][32][33][34] Treatment. Different types of treatment (surgery, radiotherapy, and drug therapy) can be specified in the model, as well as decision rules that govern the choice of treatment for a specific patient.…”
Section: Disease Modelmentioning
confidence: 99%